Hoax in Modern Politics - Pratiwi Utami (Jurnal Ilmu Sosial dan Ilmu Politik, 2018)
The propagation of hoaxes on social media has contributed to political tension in many countries. The 2016 US presidential election provides evidence of how fake news can generate more social media engagement than real news. In multicultural Indonesia, the history of anti-communist, anti-Christian, and anti-Chinese pogroms increases the level of sensitivity and sentiment, especially when dealing with racial issues. This paper explores the role of hoaxes in Indonesia’s contemporary politics. It investigates the characteristics of hoax information circulated on social media during the 2017 Jakarta election using a memetic practice approach. This study perceives hoaxes as having acted like memes in terms of the ways in which they dismantle existing source material to tap into ideas or sentiments people connect with. Hoaxes as memes alter original items into new forms of artifacts, with new messages that resonate with existing beliefs in society. Consequently, hoaxes can create a culture based on a shared belief among the community and, in the era of increasing polarization, a hoax has the potential to be a means of political partisanship. However, with the tendency to overpower the truth and lead people away from believing facts, hoaxes can be a threat to participatory democracy.